Valentin. - Valentin, 1977-; Nykänen, Anssi, 1965-; Tenkula, Kille; Sundell, Tero; Rantanen, Harri, 1960-; Virtanen, Pekka, 1964-; Niemi, Jussi (Jussi Veli Johannes); Haavisto, Olli, 1954-; Kokko, Petri (Petri Mikael); Närhi, Risto ([Helsinki] : Euromanageri, 1998)
12 kappaletta.
Valentin (lauluääni). Muusikot: Anssi Nykänen, Kille Tenkula, Tero Sundell, Harri Rantanen, Pekka Virtanen, Jussi Niemi, Olli Haavisto, Petri Kokko, Risto Närhi...
Äänitys: 1997, 1998, Studio Kaktus & Unirecords Studio.
Julkasitu myös C-kasettina.
Keywords: iskelmät; tanssimusiikki